Anti-inflammatory and antinociceptive activity of Siparuna guianensis Aublet, an amazonian plant traditionally used by indigenous communities. (30th January 2021) - Conegundes, Jessica Leiras Mota; Silva, Josiane Mello da; Mendes, Renata de Freitas; Fernandes, Maria Fernanda; Pinto, Nícolas de Castro Campos; Almeida, Maycon Alcantara de; Dib, Paula Ribeiro Braga; Andrade, Rafaela de Oliveira; Rodrigues, Matheus Nehrer; Castañon, Maria Christina Marques Nogueira; Macedo, Gilson Costa; Scio, Elita
Abstract: Ethnopharmacological relevance: Siparuna guianensis Aublet leaves, known as negramina, are used by indigenous and local communities in Brazil and other countries in the Americas to treat pain and inflammatory diseases. Aim of the study: To characterize the chemical constituents and to evaluate the antioxidant, anti-inflammatory, antinociceptive and locomotor activities of the dichloromethane fraction (DF) of S. guianensis leaves. Also, an acute oral toxicity test was accomplished. Material and methods: The chemical characterization of DF was performed by ultra-high pressure liquid chromatography (UHPLC) analyses coupled with a high-resolution mass spectrometer. The antioxidant potential of DF was investigated using nitric oxide (NO) and hydroxyl radical (OH) scavenging test. The evaluation study of the anti-inflammatory activity was carried out in vitro by NO measurement in stimulated macrophages and, in vivo, by croton oil-induced ear edema, LPS-induced peritonitis, and zymosan-induced arthritis in mice. Different mechanisms of central and peripheral nociception were stimulated by acetic acid-induced writhing, formalin, and tail-flick tests. Besides that, the open field assay was performed. Results: UHPLC analyses of DF showed the presence of a mixture of glycosylated and methoxylated flavonoids. DF was able to scavenge NO and OH radicals in vitro and showed anti-inflammatory activity by inhibiting NO production in LPS-stimulated murine macrophages. Oral administration of DF considerably inhibited the ear edema after croton oil application and reduced the leukocyte infiltrated in LPS-induced peritonitis. In the inflammatory intra-articular zymosan-induced process, DF showed a significant reduction in the inflammatory area and of the cells in the synovial and connective tissues adjacent to the joint. Also, DF was able to reduce the intra-articular edema. In nociception models, the oral administration of DF considerably inhibited the acetic acid-induced writhings. The formalin test showed that DF attenuated the licking time in both phases, which suggested that DF reduce the nociception by central and peripheral mechanisms. In the tail-flick test, DF showed no activity. Besides that, DF did not affect the animal locomotion, and no acute toxicity was observed. Conclusions: For the first time, the anti-inflammatory and antinociceptive activities of S. guianensis were reported, supporting its ethnopharmacological uses for some inflammatory diseases and painful conditions. Graphical abstract: Image 1